PENGEMBANGAN E-MODUL BERBASIS ANDROID PADA MATERI GOTONG ROYONG DALAM PEMBELAJARAN PPKN DI SEKOLAH DASAR - Fadli, Fadlizon Julian (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
Education is an important aspect in developing humans as quality resources. Citizenship education teaches about Indonesia's diversity, one of which is mutual cooperation. -module or electronic module is a module in digital form, consisting of text, images, or both containing digital electronic material. This research aims to determine the development of an Android-based E-module on mutual cooperation material in Civics learning in elementary schools. The method used is review research conducted using several previous articles. The results of this research are that after testing the validity of the e-module, it can be stated that the e-module can be used and further developed. So it can be concluded that the development of the E module is effective for use. The effectiveness of the e-module developed is very good for use in learning. From these results it can be concluded that the Android-based E-Module Development product uses Mutual Cooperation Material in Civics Learning in Elementary Schools.